Pengaruh Penambahan Minyak Jagung pada Pembuatan Keju Olahan (Sliced Cheese) dengan Koagulan Getah Pepaya Kering terhadap Kadar Air, Stabilitas Emulsi, dan Rendemen - Azzahro, Faiz Muzaki; Putranto, Wendry Setiyadi; Wulandari, Eka (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Sliced cheese is a processed cheese product that has been thinly cut or molded, usually coated with plastic or other materials. This study aimed to determine the effect of corn oil addition in the manufacture of sliced cheese with dried papaya gum (papain) coagulant on moisture content, emulsion stability, and yield. The study was conducted using a completely randomized design (CRD) with four treatments of corn oil concentration (0%, 5%, 10%, and 15%) repeated five times. ANOVA analysis showed that the addition of corn oil had no significant effect on moisture content (P>0.05), but had a significant effect on emulsion stability and yield (P<0.05). Further test using Duncan's multiple range test showed that the addition of 10% corn oil resulted in a moisture content of 35.48%, emulsion stability of 98.07%, and yield of 74.88%. The addition of corn oil was proven to increase the emulsion stability and yield of processed cheese without significantly affecting the moisture content.